Application of magnetic activated carbon for combined adsorption with 4-chlorophenol decomposition by hydrogen peroxide oxidation - Anh Kien, Le; Van Thanh Huy, Ngo; Anh Khoi, Tran; Thanh Tung, Nguyen; Thi Thuy, Nguyen; Van Linh, Nguyen (Vietnam Journal of Science and Technology, 2025)
This paper presents the synthesis of magnetic activated carbon materials using a coprecipitation method to produce ferromagnetic oxide (Fe3O4) particles attached to the activated carbon surface. The synthetic material is applied to treat 4-chlorophenol in water by an advanced oxidation process using hydrogen peroxide. Modern analysis techniques such as scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy dispersive X-ray (EDX), vibrating sample magnetometer (VSM), specific surface area and pore size distribution (BET/BJH) have been used to analyze the composition and structure of magnetic activated carbon. The results showed that the material sample had Fe3O4 crystals in the structure with a magnetization of 8.19 emu.g-1, a specific surface area BET of 330.3 m2.g-1, and a total pore volume of 0.16 cm3.g-1. The ability to oxidize 4-chlorophenol using magnetic activated carbon materials has been studied, and the results indicate that more than 86 % of 4-chlorophenol is decomposed after 60 min with the optimal conditions of pH 3.0, H2O2 and 4-chlorophenol concentration ratio of 6.8, Fe2+/Fe3+ molar ratio of 3:1, and mass fraction of Fe3O4 on activated carbon of 20 %. This shows the potential for 4-chlorophenol processing in sources discharged with magnetic catalytic materials.